PROFIL GANGLION NITRERGIK DI PLEKSUS MIENTERIKUS USUS HALUS MARMOT (Cavia sp.) : TEKNIK PEWARNAAN NADPH-d - , WIVQIE HALUM FARCHA, Dr.drh. Amelia Hana, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to determine profile of ganglion nitrergic plexus myentericus of small intestine of pig guinea (Cavia sp.) with NADPHdiaphorase staining. Animals used were five male guinea pig with an average body weight 409-554 g. Guinea pig anaesthetized with chloroform, and then killed using cervical decapitation method. Small intestine taken from abdominal dissection and divide into duodenum, jejunum and ileum. Then, every segments fixation on the formalin 10% during 60 minutes then stained with NADPH-d staining, was observed, shows the number of ganglion and neurons in ganglion using optical lab. The analysis with mean and deviation standart. The result of research in the duodenum, jejunum and ileum is average count of ganglion almost similar, count of neuron in ganglion of duodenum 7-18, in jejunum 4-16 and ileum 5-15. Ganglion is association of cell body and covered with tissue. The location of ganglion is periphery nerve system. The shape of ganglion is circle, length and square. The size of ganglion small, medium and large. The conclusion of research is profile of ganglion plexus myentericus duodenum, jejunum and ileum almost similar, so the physiology of duodenum, jejunum and ileum similar.